Supranational Governance in Changing Societies of European Union in the Last Decade - TULUS WARSITO (Jurnal Studi Pemerintahan, 2013)
As a supranational organization The European Union (EU) seems to compete the UN’s reputations. UNO has more members since its scope is worldly, but UN does not issue its own currency while EU has Euro. The Euro is the second largest reserve currency as well as the second most traded currency in the world after the United States dollar. The currency is also used in a further many European countries and consequently used daily by some 332 million Europeans. Additionally, over 175 million people worldwide - including 150 million people in Africa - use currencies which are pegged to the Euro. No other transnational organization has such a specific currency. Although not as a unified military conventional power, EU has such a “Battlegroups” initiative, each of which is planned to be able to deploy quickly about 1500 personnel. EU forces have been deployed on peacekeeping missions from Africa to the former Yugoslavia and the Middle East. EU military operations are supported by a number of bodies, including the European Defense Agency, European Union Satellite Centre and the European Union Military Staff. In an EU consisting of 27 members, substantial security and defense cooperation is increasingly relying on great power cooperation.Despite those organizational strengths, only 27 of 57 European states are members of EU. And only 17 of 27 EU state members are using Euro is their official currency. One prominent EU member like British stay tough with their own Pound-sterling.This paper is set to learn more about: why as a Europe continent based organization, EU state members are still less than half of European states? And why only 17 EU state members are using Euro as their official currency?